1984
DOI: 10.2307/3899143
|View full text |Cite
|
Sign up to set email alerts
|

Shade Tolerance of Grass and Legume Germplasm for Use in the Southern Forest Range

Abstract: A series of experiments was conducted during 1978,1979, and 1980 to screen selected cultivars of grasses and legumes for their adaptation and performance under a multiple harvest system in a shaded environment. Acceptable stands of all species except Unioh sessiliflora Michx. were obtained under each shade treatment. The most shade tolerant species were 'Nangeela' subclover (T#olium subternzneum L.), ryegrass (Lolium mul@7orium Lam.), Per&n clover (Trifolium resupinatum L.) and crimson clover (Trifolium incarn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 2 publications
(2 reference statements)
1
19
0
1
Order By: Relevance
“…Shade created by trees modifies the environment in the alleys and can affect the yield of forage crops (Pearson 1983;Watson et al 1984). Peri et al (2001) found that alfalfa dry matter production decreased by 36% under a stand of 10-11-year-old radiata pine (Pinus radiata D. Don) trees compared to the open.…”
Section: Introductionmentioning
confidence: 99%
“…Shade created by trees modifies the environment in the alleys and can affect the yield of forage crops (Pearson 1983;Watson et al 1984). Peri et al (2001) found that alfalfa dry matter production decreased by 36% under a stand of 10-11-year-old radiata pine (Pinus radiata D. Don) trees compared to the open.…”
Section: Introductionmentioning
confidence: 99%
“…Shade tolerance of subterranean clover and some other temperate legumes is based on the limited extent of yield reductions under shade [5,13]. Increased growth of Leucaena leucocephala (Lam.)…”
Section: Discussionmentioning
confidence: 99%
“…Research during the past 30 years has evaluated the potential of combining these two objectives. Evaluations of suitable pasture species [6,8,13], spacing of planted pines [6,7], and other aspects of such multiple use or agroforestry have been addressed [4,8]. Limitations of combining grazing and tree production include increased susceptibility of young, fast-growing pines to insect and disease attack when the associated pasture plants are heavily fertilized [4,6], the need for appropriate management of grazing livestock to prevent excessive damage to trees especially at high stocking rates [8], the need for shade tolerant pasture plants even though canopy closure of tree stands gradually decreases forage production even of shade-tolerant plants [8], and low wood quality of the commonly planted slash pine (Pinus elliottii Engelm.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Malkin and Fork (1981) reported that shade plants had larger chlorophyll reaction centers. Watson et al (1984) found that shade reduced the height of species with an upright growth habit more than it did the sod-forming species. Other factors such as the temporal dynamic in soil moisture or organic matter breakdown were also found to promote herbaceous plant growth under shade or in full sunlight (Wilson, 1996).…”
Section: Forage Growth Under Tree Canopymentioning
confidence: 94%